The lectin isolated from Lonchocarpus araripensis seed elicits endothelium-dependent vasorelaxation - Pires, Alana de Freitas (2017)
Background: The vasorelaxant effect of lectins from leguminous plants (Diocleinae subtribe) is well described. However, this effect has been little explored for lectins isolated from Dalbergieae tribe, except for that of Vatairea guianensis, that induces vasorelaxation involving nitric oxide and the lectin domain. Objective: To evaluate the vasorelaxant effect of a lectin isolated from Lonchocarpus araripensis (LAL), Dalbergieae tribe, and the involvement of the lectin domain and endothelium derived relaxing factors. Methods: Aortic rings of Wistar rats (250 - 300 g) were mounted in organ bath and mantained in physiological conditions (CEUA No. 10130208-8/40). LAL (0.1–100 µg/ml) was added to phenylephrine (0.1 µM)-contracted tissues with either endothelium intact or denuded. In order to investigate the mechanisms of LAL relaxation, inhibitors of NOS (L-NAME: 100 µM), cyclooxygenase (indomethacin: 10 µM), or potassium channels (TEA: 5 mM) were added to endothelized tissues 30 min before contraction. The involvement of lectin domain was assessed by previous incubation of LAL (30 µg/ml) with GlcNAc (0.1 M). Results: LAL (0.1-100 µg/ml) induced relaxation only in endothelized aorta, being maximal at 100 µg/ml (62.57 ± 7.8%). The relaxant effect induced by LAL at 30 µg/ml (52.49 ± 10.32%) was abolished by previous incubation with GlcNAc. LAL relaxant effect (IC50 9.75 ± 7.1) was partially reversed by indomethacin (IC50 LAL + indomethacin: 30.47 ± 10.93) and was abolished by L-NAME or TEA. Conclusion: LAL exhibits vasorelaxant activity in contracted endothelized aorta of rats, involving the lectin domain, muscarinic receptor of acetylcholine and endothelial derived relaxing factors.